2014
DOI: 10.1021/ja500054c
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman Spectroscopy of the Oxygenated Intermediates of Human CYP19A1 Implicates a Compound I Intermediate in the Final Lyase Step

Abstract: CYP19A1, or aromatase, a cytochrome P450 responsible for estrogen biosynthesis in humans, is an important therapeutic target for the treatment of breast cancer. There is still controversy surrounding the identity of reaction intermediate that catalyzes carbon–carbon scission in this key enzyme. Probing the oxy-complexes of CYP19A1 poised for hydroxylase and lyase chemistries using resonance Raman spectroscopy and drawing a comparison with CYP17A1, we have found no significant difference in the frequencies or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 36 publications
7
67
0
Order By: Relevance
“…Furthermore, a very recent resonance Raman study found no significant difference between the oxy-complexes of aromatase in the first and third sub-cycles implicating the involvement of Compound I in the terminal lyase step. 27 Kinetic solvent isotope effect studies of the three sub-cycles of aromatase led to an identical conclusion. 28 Both experimental and theoretical studies clearly indicate that the reactivity of CYPs is not a clear-cut mechanism.…”
Section: 19mentioning
confidence: 81%
See 1 more Smart Citation
“…Furthermore, a very recent resonance Raman study found no significant difference between the oxy-complexes of aromatase in the first and third sub-cycles implicating the involvement of Compound I in the terminal lyase step. 27 Kinetic solvent isotope effect studies of the three sub-cycles of aromatase led to an identical conclusion. 28 Both experimental and theoretical studies clearly indicate that the reactivity of CYPs is not a clear-cut mechanism.…”
Section: 19mentioning
confidence: 81%
“…27,28 A significant difference has been found in the reaction mechanism as predicted by QM-only and QM/MM calculations. According to the QM-only calculations 1β-hydrogen is abstracted by …”
Section: Resultsmentioning
confidence: 99%
“…An example is the use of resonance Raman spectroscopy to reveal control of regio- and stereo- specificity of catalysis, which would be impossible with a highly heterogeneous or aggregated sample. 82,86,87,89 …”
Section: Application Of Nanodiscs In Functional Studies Of Membranmentioning
confidence: 99%
“…An exhaustive list of spectroscopic techniques will not be discussed in this section, but another technique worth mentioning is resonance Raman spectroscopy, which selectively measures the vibrational modes of the heme group in P450 enzymes. This technique was used to observe the different P450 species depending on the substrate used [25, 26]. …”
Section: Stopped-flow Technique (Steps 1 2 9 – Substrate Bindingmentioning
confidence: 99%